2019
DOI: 10.1007/s00408-019-00211-w
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase-Type Plasminogen Activator Receptor and Arterial Stiffness in Patients with COPD

Abstract: Introduction Soluble urokinase-type plasminogen activator receptor (suPAR) is upregulated by inflammation and plays a role in the pathogenesis of atherosclerosis. Chronic obstructive pulmonary disease (COPD) is associated with enhanced systemic inflammation and increased risk for atherosclerosis, however, studies analysing the circulating suPAR levels in COPD are contradictory. The aim of the study was to investigate plasma suPAR concentrations together with markers of arterial stiffness in COPD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Still, our results should be interpreted carefully, especially considering the exclusion of the two outliers which resulted in differences between the two groups. The sample size calculations were based on our previous study [25], showing higher suPAR levels in COPD. Although the number of participants may seem low, it may not be the likely reason for the lack of differences between OSA and controls considering the wide overlap of suPAR values between the two groups and the lack of significant relationship between markers of OSA severity and suPAR levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, our results should be interpreted carefully, especially considering the exclusion of the two outliers which resulted in differences between the two groups. The sample size calculations were based on our previous study [25], showing higher suPAR levels in COPD. Although the number of participants may seem low, it may not be the likely reason for the lack of differences between OSA and controls considering the wide overlap of suPAR values between the two groups and the lack of significant relationship between markers of OSA severity and suPAR levels.…”
Section: Discussionmentioning
confidence: 99%
“…Within 30 minutes, blood samples were centrifuged at 4 • C for 10 min at 1500 rpm, and the plasma was stored at −80 • C until further analysis. Plasma suPAR levels were measured using a commercially available ELISA kit (ViroGates A/S, Birkerød, Denmark) as described previously [25]. The samples were measured in duplicates, and the mean concentration was used.…”
Section: Supar Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies included participants from the outpatient department, 12 , 22 , 25 , 27 , 28 and four included participants from the respiratory medicine. 23 , 26 , 29 , 31 In terms of pulmonary function, six studies included patients with predicted FEV1% ⩾80%, 12 , 22 , 23 , 26 28 and another five studies reported patients with the predicted FEV1% < 80%. 12 , 25 , 29 31 The studies reported that the smoking status of patients ranged from 28 to 53 packs per year.…”
Section: Resultsmentioning
confidence: 99%
“…27 A recent study has shown that suPAR concentrations in COPD patients correlate with forced expiratory volume in 1 second (FEV 1 ), Tiffeneau Index as well as Medical Research Council Dyspnea Score. 28 Of note, suPAR was further elevated in patients with more than two exacerbations per year. 28 Several intrinsic risk factors for COPD readmission are known, including low FEV 1 , hypoxia and comorbidities.…”
Section: Discussionmentioning
confidence: 98%